1995
DOI: 10.1164/ajrccm.152.6.8520764
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of breath components in neighboring breaths of normal eupneic subjects.

Abstract: To determine the fraction of variational activity that is correlated on a breath-to-breath basis from uncorrelated random fluctuations, we performed autocorrelation analysis in 33 normal subjects during resting breathing. A calibrated inductive plethysmograph was used to nonobtrusively record 700 breaths in each subject. The group mean autocorrelation coefficients at a lag of 1 breath for each of the three primary breath components, tidal volume (VT), inspiratory time (TI), and expiratory time (TE), were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…Breath-to-breath variability is a normal characteristic of ventilation that reflects the degree of freedom-and therefore the adaptability-of the ventilatory control system (6,27,28). A decreased variability is associated with respiratory disease in adults (29) and in infants (22), and a lower variability is a predictor of weaning failure (30).…”
Section: Respiratory Variabilitymentioning
confidence: 99%
“…Breath-to-breath variability is a normal characteristic of ventilation that reflects the degree of freedom-and therefore the adaptability-of the ventilatory control system (6,27,28). A decreased variability is associated with respiratory disease in adults (29) and in infants (22), and a lower variability is a predictor of weaning failure (30).…”
Section: Respiratory Variabilitymentioning
confidence: 99%
“…Thus, PSV may adapt to breath-to-breath variability [27] more precisely than APCV, where the mechanical inflation stops after a preset time. However, the present authors found no differences in the patient/ ventilator interaction [28] (e.g.…”
Section: Pressure Support Ventilation and Assist Pressure Control Venmentioning
confidence: 99%
“…Since variability in complex living systems is not only an artefact of biological noise but also an intrinsic property of various control mechanisms, different types of deterministic (nonrandom) variability have been described in the pattern of breathing. These types include correlated and oscillatory fractions [12][13][14].…”
Section: Linear Methodsmentioning
confidence: 99%